THE LEXICAL MEANINGS OF SUBDIALECTS EXPRESSING SUBJECTIVE EVALUATION IN THE RUSSIAN LANGUAGE (Journal of Foreign Language Studies, 2019)
This article analyzes the lexical meanings of subdialects expressing a speaker’s subjective evaluation. The corpus used in this research includes two dictionaries: the Dictionary of vocabulary in Russian folk speech conveying subjective evaluation (edited by O.I. Litvinikova) and the Dictionary of Russian folk subdialects (in 40 volumes). There are a small number of studies conducted to analyze the semantic meanings of subdialects based on individual database, none of which has addressed the lexical groups stated in the common ground of all subdialects. This article aims to provide a comprehensive analysis of subdialects (frequently-used groups, their ability to explain and express feelings) selected from the above-mentioned corpus through random sampling method.
Keywords: word formation; subjective evaluation.; subdialects